P192 Prevalence and factors associated with impaired food-related quality of life: a cross-sectional survey of 1223 people with inflammatory bowel disease. (25th January 2019) - Czuber-Dochan, W; Murrells, T; Morgan, M; Lomer, M; Lyndsay, J O; Whelan, K
Abstract: Background: Inflammatory bowel disease (IBD) patients often report that dietary intake and the enjoyment of food is affected by their condition. However, the prevalence of impaired food-related quality of life (FR-QoL) and associated factors have not been previously explored. This study aimed to determine the levels of FR-QoL and factors associated with it in a large, nationally representative sample of people with IBD. Methods: A convenience sample of 1576 IBD outpatients ≥16 years old were recruited from seven UK centres. Patients consuming the majority of their intake as food completed previously validated questionnaires to capture demographic data, FRQoL-29, quality of life (IBDQ UK), IBD-distress (IBD-DS), IBD-fatigue (IBD-F), and anxiety and depression (HADS). A health professional recorded disease activity (HBI, SCCAI), disease classification (Montreal), blood results, body mass index and malnutrition risk (MUST). FR-QoL was regressed onto the explanatory variables (univariable/multivariable) using the Stata MI (20 imputed datasets) procedure. Results: Data from 1223 patients were available (78% response, 65% CD and 51% female). FR-QoL mean score was 80.1 [SD 26.9] (minimum 29, maximum 145, higher score = better FR-QoL), considerably lower in comparison to previously measured healthy volunteers [123.0, SD 16.5]. The four items rated as the most severe (Strongly agree/Agree) were 'avoiding food and drink I know does not agree with my IBD' (71%), 'being more aware of what I am eating due to my IBD' (70%), 'certain foods have triggered symptoms of my IBD' (69%) and 'enjoyment of a particular food or drink has been affected by the knowledge that it might trigger my IBD symptoms' (67%). Twenty-six factors (demographic, clinical, drug-related, psycho-social) were significantly associated with impaired FR-QOL in univariate analysis. However, in the multi-variable regression, only lower educational level ( p < 0.001), greater number of IBD flares in last 2 years ( p < 0.001), more severe symptoms during last flare ( p = 0.034), not taking immune suppressants ( p = 0.026), greater distress ( p < 0.001), greater fatigue impact on daily living ( p = 0.025) and worse IBD QoL ( p < 0.001) remained significantly associated with impaired FR-QoL. Conclusions: In this first large study reporting FR-QoL in IBD, many factors were identified as having a significant negative effect on patients with IBD. Understanding the relationship between IBD and FR-QoL may improve communication between health professionals and patients regarding its impact.